Writing of monographs of the students of the National University of San Cristóbal de Huamanga - Morales Gutiérrez, Fredy (2020)
The work entitled Writing of monographs of the students of the Faculty of Education Sciences of the National University of San Cristóbal de Huamanga was carried out with the aim of critically reflecting on the writing of monographs in a context where it is important to develop skills for the transmission of knowledge in the written plane of the language. This practice of writing must be limited to international standards, which allow the development of writing as a means of transmitting knowledge, in accordance with international references and standards, which guide the works of the monographs, with due authenticity and originality. Among the materials and methods that were used were the qualitative method, through the techniques of recording and the analysis of the content of the readings and the content, through the design of holistic-transdisciplinary research. The results we arrive at highlight that the students still do not adequately handle both the form and the content in the writing of the monographs, nor do they still use the bibliographic references adequately, both within the work and in the final references. The conclusions of the work highlight that in the Faculty of Educational Sciences, work should be done systematically among the professors who develop scientific writing courses.